Vow of justice - Eason, Lynette (Eason, Lynette. Blue justice, 2019)
"When Allison Radcliffe is killed, FBI Special Agent Linc St. John goes after her killer with a vengeance until he discovers she's been in hiding. He must put aside their unfinished business before she becomes the next victim"--